Effect of 0.4% Triphala and 0.12% chlorhexidine mouthwash on dental plaque, gingival inflammation, and microbial growth in 14–15-year-old schoolchildren: A randomized controlled clinical trial - Ketaki Bhor; Vittaldas Shetty; Vikram Garcha; Kadambari Ambildhok; Vineet Vinay; Gargi Nimbulkar (Journal of Indian Society of Periodontology, 2021)
Context: A strong correlation exists between plaque and dental caries and periodontal diseases. Ayurvedic drugs have been used since ancient times; oral rinses made from these are used in periodontal therapy. Triphala is one of these with wide spectrum of activity. Aims: To assess and compare the effect of 0.4% Triphala and 0.12% chlorhexidine (CHX) mouthwash on dental plaque, gingival inflammation, and microbial count of Streptococcus mutans, Streptococcus sanguinis, and Lactobacilli from dental plaque sample of 14–15-year-old schoolchildren of Pune city during 90 days supervised use. Settings and Design: A randomized, controlled, double-blind, parallel-group clinical trial was conducted among 72 schoolchildren aged 14–15 years. Subjects and Methods: Children were divided into two study groups: Group A with 0.4% Triphala mouthwash (n = 36) and Group B with 0.12% CHX mouthwash (n = 36). The plaque Index (Loe H [1967]), gingival index (Loe H and Silness J [1963]), and microbial analysis were recorded at baseline, 30 days, and 90 days interval. Statistical Analysis Used: Statistical analysis was done using unpaired t-test for group-wise comparison and one-way analysis of variance test, followed by Tukey's post hoc test for intragroup comparison. P < 0.05 was considered statistically significant. Results: The results showed that 0.4% Triphala and 0.12% CHX have similar inhibitory effect on plaque accumulation, gingivitis, and growth of S. mutans, S. sanguinis, and Lactobacilli. Conclusion: Herbal mouthwash proved to be helpful in reducing plaque microbial counts, plaque, and gingival inflammation and opens new arenas in the field of herbal dentistry and chemical plaque control.